2003
DOI: 10.1080/713603220
|View full text |Cite
|
Sign up to set email alerts
|

Insulin secretion and insulin sensitivity in normal pregnancy and gestational diabetes mellitus

Abstract: The purpose of this study was to evaluate insulin sensitivity, beta-cell function and islet-cell-directed autoimmunity in pregnant women with normal glucose tolerance and gestational diabetes mellitus (GDM). A total of 21 women with normal glucose tolerance and 21 women with GDM were evaluated at 24-36 weeks' gestation. Insulin resistance and beta-cell function were evaluated using the continuous infusion of glucose with model assessment (CIGMA) method, which aims to give a near-physiological stimulus and to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…GDM can seriously threaten the health of mothers and offspring [36]. Although the pathogenesis remains unclear, related studies have shown that insulin resistance is mainly caused by a series of physiological and pathological changes during pregnancy [37]. Adipose tissue is resistant to insulin action, resulting in lower levels of insulin receptors in fat [38,39] and the number of insulin receptors in the body gradually decreases with increasing BMI.…”
Section: Discussionmentioning
confidence: 99%
“…GDM can seriously threaten the health of mothers and offspring [36]. Although the pathogenesis remains unclear, related studies have shown that insulin resistance is mainly caused by a series of physiological and pathological changes during pregnancy [37]. Adipose tissue is resistant to insulin action, resulting in lower levels of insulin receptors in fat [38,39] and the number of insulin receptors in the body gradually decreases with increasing BMI.…”
Section: Discussionmentioning
confidence: 99%
“…GDM and type 2 diabetes are closely related, confer a common pathogenesis of insulin resistance and/or β‐cell function, and have been focused on worldwide because of their potential long‐term adverse effects on pregnant women and their offspring, such as obesity, metabolic syndrome, and increased risk for cardiovascular disease . Cross‐sectional studies have shown that the degree of insulin resistance increases and β‐cell function decreases in GDM patients as their pregnancy progresses . However, data on glucose metabolism among pregnant women with normal blood glucose and those with GDM are limited.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Crosssectional studies have shown that the degree of insulin resistance increases and b-cell function decreases in GDM patients as their pregnancy progresses. 6,7 However, data on glucose metabolism among pregnant women with normal blood glucose and those with GDM are limited. Most studies have evaluated insulin resistance using only fasting glucose and fasting insulin levels.…”
Section: Introductionmentioning
confidence: 99%